Effect of smoking on PEFR: a comparative study among smokers and non smokers in an urban slum community of Hyderabad, India - Sawant, Gokuldas V.; Kubde, Saurabh R.; Kokiwar, Prashant R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Smoking is hazardous for health. The first impact of smoking is on lungs where it starts decreasing the lung capacity of the smokers. Hence if we can identify this decrease in lung capacity, at an early stage among the smokers, we can try to prevent the further effects of smoking on all body systems. The objective of the study was to study the effect of smoking on PEFR among smokers and compare with age, sex and other facts matched controls (non smokers) in an urban slum community of Hyderabad, India. Methods:A community based cross sectional comparative study was carried out among 50 smokers and 50 age, sex and other factor matched non smokers. Detailed history was taken. Lung capacity was measured by Wright’s peak flow meter as per the standard guidelines. Statistical tests like odds ratio and chi square were used wherever applicable. Results: The mean age and BMI of smokers and non smokers were comparable. PEFR in smokers was significantly low compared to non smokers. Smoking is strongly associated with the abnormal PEFR. The prevalence of abnormal PEFR was 84% among smokers as compared to 60% among non smokers. The smokers were found to be 3.33 times more at risk of having abnormal PEFR than non smokers. This association was statistically significant. (p < 0.05). Conclusions:The smokers were found to have reduced lung capacity compared to non smokers. Smoking is known to reduce the lung capacity. This study has proved that smoking adversely affects the normal functioning of lungs which leads to increased morbidity and mortality among smokers. Thus smoking was found to be directly related to reduced lung capacity measured in terms PEFR.